New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae) - Winkler, Daniel (Zootaxa, 2017)
Systematic soil fauna survey of riverine and swamp woodland habitats in West Hungary provided the opportunity to describe the new species L. isabelleae sp. nov. belonging to the the Lepidocyrtus pallidus-serbicus group. The new species is characterized by the dorsal macrochaetae formula R0R1sR1R2STSo/00/0101+2, the absence of scales on the antennae and legs beyond coxae and an additional dorsolateral macrochaeta (a7) on Abd. III. On this occasion, the L. pallidus-serbicus group has been revised and reinterpreted, and a differentiation key for the derived L. serbicus group has been developed.